Learning Motivation and Student Engagement Among Senior High School Students - Fakhri, Nurfitriany; Syarifuddin, Nurhidayah; Dewi, Eva Meizara Puspita; Buchori, Sahril (STKIP Andi Matappa, 2023)
The objective of this research is to ascertain the levels of learning motivation (X) and student engagement (Y) among students enrolled at SMAN X Gowa. The present investigation employed a quantitative methodology, utilizing a simple random sampling technique to procure participants for the study. The sample population for this research comprised of 150 students from SMAN X Gowa, consisting of 69 male and 81 female participants. The present investigation employed Academic Motivation Scale (AMS) and Student Engagement in School Scale. The study used the product moment method for data analysis and obtained a statistically significant positive correlation (r = 0.783, p < 0.05) between learning motivation and student engagement. The findings suggest a positive correlation between the scores of learning motivation and student involvement. The degree of motivation to learn has been found to have a significant impact on student engagement, accounting for 61.3% of the variance in this construct. The findings of this study hold significant implications that can be properly considered by educators in designing effective learning curricula.